A mathematical description of the arrhythmia of the heart - Kaganov, VI (Journal of Cardiovascular Medicine and Cardiology, 2019)
The problem of synchronization of oscillations of various physical nature is discussed. From the standpoint of the theory of synchronism, the model of the heart is considered as a system of four interconnected between self-oscillatory objects: two atria and two ventricles. The synchronous and asynchronous modes of operation with sinusoidal and relaxation oscillations are considered. A computer program simulating the electrical oscillations occurring in the heart has been compiled using four differential equations. Examples of calculation by the program are given for asynchronous and synchronous modes of operation. The possibility of evaluating the ablation procedure from the standpoint of a computer model mate is discussed.